2000
DOI: 10.1038/sj.jhh.1000981
|View full text |Cite
|
Sign up to set email alerts
|

Role of prostaglandins in hypertension

Abstract: The role of prostaglandins (PGs) in hypertension (HT) is reviewed, emphasising their biochemical characteristics, physiological effects and functions, especially in the cardiovascular area, and the current evidence of their participation in the antihypertensive activity of a

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 25 publications
(40 reference statements)
0
4
0
Order By: Relevance
“…Prostaglandins (PGs) are important modulators of inflammatory responses. For example, a variety of hormones, cytokines, and growth factors enhance synthesis of PGs, which serve as autacoids, mediating a variety of responses in the cardiovascular system (Colina-Chourio et al, 2000). PG synthesis is a multistep process, controlled by several important rate-limiting enzymes; an important and extensively studied process involves activation of PLA 2 , which catalyzes the release of arachidonic acid (AA) from phospholipids in membranes (Dennis, 1997 andBingham andAusten, 1999).…”
mentioning
confidence: 99%
“…Prostaglandins (PGs) are important modulators of inflammatory responses. For example, a variety of hormones, cytokines, and growth factors enhance synthesis of PGs, which serve as autacoids, mediating a variety of responses in the cardiovascular system (Colina-Chourio et al, 2000). PG synthesis is a multistep process, controlled by several important rate-limiting enzymes; an important and extensively studied process involves activation of PLA 2 , which catalyzes the release of arachidonic acid (AA) from phospholipids in membranes (Dennis, 1997 andBingham andAusten, 1999).…”
mentioning
confidence: 99%
“…Prostaglandins elicit many effects throughout the body, including constriction and relaxation of smooth muscles and regulation of the immune response. 6,7 Early studies analyzing the effects of prostaglandins in the eye revealed significant irritation and initial IOP elevation. Whereas the prevailing thought in the early 1970s was that prostaglandins elevate IOP, it was not until 1977 when Drs.…”
Section: Identifying Prostaglandins As Ocular Hypotensive Agentsmentioning
confidence: 99%
“…The role of prostaglandins (PGs) in blood pressure regulation has been well studied. 3 The imbalances between vasodilator and vasoconstrictor PGs may affect blood pressure. 4 On the partial basis of their ability to inhibit PG production, nonsteroidal anti-inflammatory drugs (NSAIDs) have been postulated to increase blood pressure.…”
Section: H Ypertension Is a Majormentioning
confidence: 99%